The Syriac Christianization of a Medical Greek Recipe: From Barbaros Hera to the “Apostles’ Ointment” - Asade, Daniel; Druille, Paola (Studia Ceranea, 2021)
During the Late antiquity, several works by Galen (2nd–3th CE.) were translated into Syriac for the first time by Sergius of Rēšʽaynā (6th CE.), starting up the Hippocratic-Galenic medicine in Syriac Language. Based on these translations, there arouse novel versions of compound medicines in Syriac, such as the “Apostles’ Ointment” which is found in The Book of Medicines, possibly from Abassid period, edited and translated by E.A.W. Budge in 1913, which contains more ancient Syriac medical prescriptions. The textual pharmaceutical study regarding the therapeutic uses and qualitative composition of the ‘Apostles’ Ointment’, and its comparison with a kind of plaster (barbaros) which appears in various Late antiquity Greek recipes (Galen, Oribasius, Aetius of Amida, and Paul of Aegina), reveal the micro-transformations suffered to a new and final Syriac Christian version which we here introduce.